Living lab catalyst for urban regeneration - Tantuico, Raisa Margarita S. (College of Architecture, University of the Philippines Diliman, 2014)
This research took off with the relief that the problem of informal settlers and urbanization in Metro Manila is a multi-faceted problem that cannot be answered by housing alone. This research examines the conventional tools in housing programs in the Metro Manila, and uses its theoretical framework as basis to approach the deign problem: What design of a structure for underserved communities can bring about social and economic transformation while being adaptive and responsive to the community it serves? It mainly takes a bottom-up approach to housing, giving opportunity to the community to become active participants in the entire process. The resulting design takes from the concept of a matrix framework where there is a main structural frame and various levels of plug-in take place. Its modularity and kit of parts approach allows for it to be replicated and scaled to other future sites of interventions.